A High Precision Software Compensation Algorithm for Silicon Piezoresistive Pressure Sensor. Issue 4 (1st July 2019) - Wu, Tianshu; Chen, Shuyu; Wu, Peng; Nie, Shaozhong
Abstract : There are generally zero drift, sensitivity drift and nonlinear error in silicon piezoresistive pressure sensors due to the inherent characteristics of semiconductor materials. It is necessary to compensate and correct the errors produced so as to meet the requirements of measurement accuracy. In order to further improve the compensation precision, based on the research of various basic software compensation methods, a surface fitting compensation algorithm based on least square method is designed, and the software is implemented on the Visual Basic platform. The experimental results show that the zero drift, sensitivity drift and nonlinear error is effectively eliminated, and the output precision of the sensor is greatly improved.